2023
DOI: 10.1021/acs.estlett.3c00383
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanoscale Crystallinity on the Recovery of Rare Earth Elements (REEs) from Coal Fly Ash

Sheila Gerardo,
Kevin Matthews,
Jamie Warner
et al.

Abstract: Reclamation of coal fly ash, a legacy waste material, provides an alternative pathway for the recovery of rare earth elements (REEs) while reducing the environmental stresses that stem from traditional mining. The reactive transport processes underlying the recovery of REEs from ash wastes, however, are yet to be fully elucidated owing to the physicochemical complexity of the micro/nanoscale fly ash particles, including the crystallinity of the particulate matrix. In this work, we use transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Results here indicate that the REE species are not significantly transformed during the combustion process and the more refractory phosphate minerals, such as xenotime and monazite, or silicate minerals, such as zircon, are preserved and are dispersed throughout the ash particles. There is evidence that crystallographic controls such as porosity can play a role in REE extractability, and that more porous ash particles may arise from the crystalline structure of clays preserved during combustion . Findings from this study in conjunction with those mentioned above provide strong evidence that the major REE-bearing minerals are transferred from the coal into the ashes through combustion and are distributed among different bulk phases in the ash particle.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Results here indicate that the REE species are not significantly transformed during the combustion process and the more refractory phosphate minerals, such as xenotime and monazite, or silicate minerals, such as zircon, are preserved and are dispersed throughout the ash particles. There is evidence that crystallographic controls such as porosity can play a role in REE extractability, and that more porous ash particles may arise from the crystalline structure of clays preserved during combustion . Findings from this study in conjunction with those mentioned above provide strong evidence that the major REE-bearing minerals are transferred from the coal into the ashes through combustion and are distributed among different bulk phases in the ash particle.…”
Section: Resultssupporting
confidence: 63%
“…Analysis by SEM-EDS and XANES identified the presence of phosphate minerals which may include monazite/rhabdophane and xenotime/churchite . Scanning transmission electron microscopy EDS of fly ash from Powder River Basin coal demonstrated that REE were hosted in monazite . Electron probe microanalysis (EPMA) and SEM-EDS have identified individual crystals of the REE-phosphate minerals rhabdophane, monazite, and xenotime in the fly ash matrix or encapsulated by the aluminosilicate glass which may have been unaffected by the combustion process since their melting points are above the combustion temperatures …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the current leaching technique has a low recovery rate (40%-60%), due to the leakage of REE uids in undesirable directions. Hence, new approaches to mine REEs more effectively and sustainably are urgently needed 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%